Synthesis of academic and modern practices of learning sculpture in creative universities of kazakhstan - Meldesh, Gulfiya (Pedagogy and Psychology, 2021)
The article put attention on the need for a methodological collaboration analysis of the academic and modern types of teaching sculpture in the specialized creative colleges and universities of the Republic of Kazakhstan in the modern educational and aesthetic discourse. The main research problem focuses on identifying and characterizing the most relevant educational theoretical and practical methods that can significantly increase the level of domestic art education in the art of sculpture. The author believes that a comprehensive scientific analysis of the educational potential of the Kazakhstani aesthetic originality of modern sculpture, its history and technical and technological features will give a possibility to understand deeply and see the big picture of the art education role in the general socio-cultural canvas of sovereign Kazakhstan. At the moment, the Kazakhstani art education system is on a peripeteia and it is necessary to clear the choice between academic and contemporary art practices or their harmonious synthesis. This work is devoted to these question’s analysis and the author's research work disclosure.